Un sigillum enigmatico: Amm. XXXI, 16, 9 (Gilgameš, 2019)
Many scholars have written about Amm. XXXI, 16, 9, paragraph inwhich Ammianus qualifies himself as miles quondam et Graecus.Generally, it is possible to distinguish two interpretations: it couldbe a biographic reference or an apology due to his presumedincompetence as latin writer. Starting from the comparisonbetween the whole passage, the two prefaces (XV, 1, 1 and XXVI, 1,1-2) and other chapters, this paper wants to stress the complexityof Ammianus work and his awareness as a literary man, givingparticular importance to the adverb quondam.